Irradiation of necrotic cancer cells, employed for pulsing dendritic cells (DCs), potentiates DC vaccine-induced antitumor immunity against high-grade glioma - Vandenberk, Lien (Oncoimmunology, 2015)
Dendritic cell (DC)-based immunotherapy has yielded promising results against high-grade glioma (HGG). However, the efficacy of DC vaccines is abated by HGG-induced immunosuppression and lack of attention toward the immunogenicity of the tumor lysate/cells used for pulsing DCs. A literature analysis of DC vaccination clinical trials in HGG patients delineated the following two most predominantly applied methods for tumor lysate preparation: freeze-thaw (FT)-induced necrosis or FT-necrosis followed by X-ray irradiation. However, from the available clinical evidence, it is unclear which of both methodologies has superior immunogenic potential. Using an orthotopic HGG murine model (GL261-C57BL/6), we observed that prophylactic vaccination with DCs pulsed with irradiated FT-necrotic cells (compared to FT-necrotic cells only) prolonged overall survival by increasing tumor rejection in glioma-challenged mice. This was associated, both in prophylactic and curative vaccination setups, with an increase in brain-infiltrating Th1 cells and cytotoxic T lymphocytes (CTL), paralleled by a reduced accumulation of regulatory T cells, tumor-associated macrophages (TAM) and myeloid-derived suppressor cells (MDSC). Further analysis showed that irradiation treatment of FT-necrotic cells considerably increased the levels of carbonylated proteins — a surrogate-marker of oxidation-associated molecular patterns (OAMPs). Through further application of antioxidants and hydrogen peroxide, we found a striking correlation between the amount of lysate-associated protein carbonylation/OAMPs and DC vaccine-mediated tumor rejection capacity thereby suggesting for the first time a role for protein carbonylation/OAMPs in at least partially mediating antitumor immunity. Together, these data strongly advocate the use of protein oxidation-inducing modalities like irradiation for increasing the immunogenicity of tumor lysate/cells used for pulsing DC vaccines.